2017
DOI: 10.1038/srep44923
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization reveals the complexity of previously overlooked coral-exosymbiont interactions and the implications for coral-guild ecology

Abstract: Several obligate associate crabs and shrimps species may co-occur and interact within a single coral host, leading to patterns of associations that can provide essential ecological services. However, knowledge of the dynamics of interactions in this system is limited, partly because identifying species involved in the network remains challenging. In this study, we assessed the diversity of the decapods involved in exosymbiotic assemblages for juvenile and adult Pocillopora damicornis types α and β on reefs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The two divergent genetic lineages show a parapatric latitudinal distribution: one extends from southern Peru (17°S) to central Chile (30°S), and the other from central Chile (29°S) to Chiloe Island (42°S), both lineages spatially overlapping in a narrow area (29-30°S) in discrete patches where individuals belong to either the northern or southern species. Likewise, studying the ecological interactions between a coral host and its crustacean exosymbionts, Rouzé et al (2017) used barcoding methods to identify the exosymbionts and found two cryptic species in the shrimp Alpheus lottini, revealing the key role of cryptic diversity in structuring communities of mutualists and the importance of taking into account this diversity in ecological studies to better perceive the complexity of ecological processes. Similarly, Souter, Henriksson, Olsson, and Grahn (2009) studied the connectivity pattern in the coral Pocillopora damicornis in East Africa and, after identifying two cryptic lineages using mitochondrial markers, chose to analyze them separately.…”
mentioning
confidence: 99%
“…The two divergent genetic lineages show a parapatric latitudinal distribution: one extends from southern Peru (17°S) to central Chile (30°S), and the other from central Chile (29°S) to Chiloe Island (42°S), both lineages spatially overlapping in a narrow area (29-30°S) in discrete patches where individuals belong to either the northern or southern species. Likewise, studying the ecological interactions between a coral host and its crustacean exosymbionts, Rouzé et al (2017) used barcoding methods to identify the exosymbionts and found two cryptic species in the shrimp Alpheus lottini, revealing the key role of cryptic diversity in structuring communities of mutualists and the importance of taking into account this diversity in ecological studies to better perceive the complexity of ecological processes. Similarly, Souter, Henriksson, Olsson, and Grahn (2009) studied the connectivity pattern in the coral Pocillopora damicornis in East Africa and, after identifying two cryptic lineages using mitochondrial markers, chose to analyze them separately.…”
mentioning
confidence: 99%
“…Second, stability can also be the ability of the system to retain the remaining N -1 species, should one of the participating species go extinct. Third, stability can also refer to the ability of the system to resist intrusion into the community from non-associated species (Case, 1990;Bascompte et al, 2006;Fontaine et al, 2011;Coyte et al, 2015;Mougi, 2016;Rouze et al, 2017). Lastly, stability can also refer to change in the species composition in a niche, when the environment changes.…”
Section: Introductionmentioning
confidence: 99%